2022
DOI: 10.1016/j.biocel.2021.106135
|View full text |Cite
|
Sign up to set email alerts
|

Odd chain fatty acid metabolism in mice after a high fat diet

Abstract: Epidemiological studies show that higher circulating levels of odd chain saturated fatty acids (FA: C15:0 and C17:0) are associated with lower risk of metabolic disease. These odd chain saturated fatty acids (OCSFA) are produced by α-oxidation in peroxisomes, de novo lipogenesis, from the diet and by gut microbiota. Although present at low concentrations, they are of interest as potential targets to reduce metabolic disease risk. To determine whether OCSFA are affected by obesogenic diets, we have investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In several epidemiological studies, C15:0 and C17:0 have been shown to inversely correlate with NAFLD and other metabolic diseases, Pfeuffer & Jaudszus (2016); Mika et al (2016); Yoo et al (2017) . As demonstrated in our previous study that high dietary fat (HFD) intake reduces serum and liver OCFA, OCFA- producing gut microbiota and is associated with impaired liver lipid metabolism Ampong et al (2021) . Methionine adenosylated product, S -adenosylmethionine is a known substrate for methylation in epigenetic and epigenomic pathways, Robinson et al (2016) , and methylation has been linked to NAFLD directly and indirectly via PPARg.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In several epidemiological studies, C15:0 and C17:0 have been shown to inversely correlate with NAFLD and other metabolic diseases, Pfeuffer & Jaudszus (2016); Mika et al (2016); Yoo et al (2017) . As demonstrated in our previous study that high dietary fat (HFD) intake reduces serum and liver OCFA, OCFA- producing gut microbiota and is associated with impaired liver lipid metabolism Ampong et al (2021) . Methionine adenosylated product, S -adenosylmethionine is a known substrate for methylation in epigenetic and epigenomic pathways, Robinson et al (2016) , and methylation has been linked to NAFLD directly and indirectly via PPARg.…”
Section: Discussionmentioning
confidence: 84%
“…However, in recent times, OCFA have been suggested as important targets to improve metabolic diseases in part due to their inverse association with several cardiometabolic events. In addition to the gut microbiota and diet suggested as potential source of OCFA, several metabolic pathways including phytanoyl-CoA α-hydroxylase (PHYH) , 2-hydroxyphytanoyl-CoA lyase (HACL1) ; pristanal dehydrogenase, branched-chain alpha-keto acid dehydrogenase (BCKDHA) are known to be involved in their synthesis Ampong et al (2021) .…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, synthesis of fatty acids by the fatty acid synthase complex occurs in two carbon units meaning that only even acyl chains are produced by de novo lipid synthesis, whereas odd chain fatty acids such as C15 and C17 carbon chains typically come from dietary origins or are produced by the gut microbiota. In mice on HFD, C15 and C17 fatty acids are decreased and correlated with lower abundance of several gut microbial species including Lactobacillus, Bifidobacterium, and Akkermansia that are known to produce these odd chain fatty acids [ 43 ]. However, other studies have shown that in humans C15 and C17 lipids are independently derived from dietary intake or α-oxidation in the persoxisome, respectively [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Odd chain saturated fatty acids are produced by α-oxidation in peroxisomes, de novo lipogenesis, from the diet and by gut microbiota. Although present at low concentrations, epidemiological studies show that higher circulating levels of odd chain saturated fatty acids (FA: C15:0 and C17:0) are associated with lower risks of metabolic diseases [ 21 ].…”
Section: Discussionmentioning
confidence: 99%